Three essays on the use of spatial data to inform environmental and resource management - Sheng, Di, author; Suter, Jordan F., advisor; Manning, Dale T., committee member; Goemans, Christopher G., committee member; Bailey, Ryan T., committee member (Colorado State University. Libraries, 2022)
This dissertation consists of three essays that use of spatial data to inform trade-offs related to environmental and resource management. The first essay explores how a spatially targeted differentiated payment design can reduce the social cost of achieving a given level of ecosystem service (ES) provisions. Performance comparisons between uniform payments and differentiated payments for ecosystem services help to identify the context under which differentiated payments offer the largest advantage relative to a uniform payment. A mathematical programming model is developed to explore the performance of different payment schemes and to derive generalized lessons from simulations. Then generalized lessons are evaluated with two case studies related to water quality management. It is found that the simulations and case studies align with each other in terms of the total cost reductions, but they diverge in the payment rate choice due to the underlying distributional differences. The findings suggest that a higher payment rate for parcels that systematically provide higher levels of ES can reduce the social cost of providing the ES of interest, particularly for cases where the mean ES provision benefits across land types are different and ES provision targets are relatively low. In the second essay, I examine whether China's pilot carbon emission trading system (ETS) has the co-benefit of reducing local PM2.5 levels. Two ETS pilot provinces are selected to be the treated group, while the control group is constructed with institutional knowledge. Static and dynamic difference-in-differences designs are adopted and compared to reveal the ETS treatment effect. The spatial and temporal variation in the ETS pilot areas allows me to adopt a dynamic two-way fixed effects model to estimate heterogeneous treatment effects on the treated areas. I find that the ETS improves the local air quality in Hubei but not in Guangdong. A further analysis suggests that a sector-standards based allowance allocation mechanism can cause local air quality to deteriorate. The third essay revisits the groundwater resource value question in the Ogallala aquifer through estimation of an econometric model of agricultural land prices that includes fixed effects, with the repeated transactions from the ZTRAX data product. Saturated thickness is used to present the groundwater availability and the study includes irrigated parcels only. Heterogeneous responses in land values to groundwater stock changes are found across Colorado and Nebraska. The marginal value of groundwater stock is highest at low levels of groundwater availability, which implies that additional groundwater depletion in Colorado is more costly than depletion in Nebraska.